2013
DOI: 10.1007/s13676-013-0024-2
|View full text |Cite
|
Sign up to set email alerts
|

POPMUSIC for the world location-routing problem

Abstract: POPMUSIC-partial optimization metaheuristic under special intensification conditions-is a template for tackling large problem instances. This template has been shown to be very efficient for various combinatorial problems like p-median, sum of squares clustering, vehicle routing and map labelling. In terms of algorithmic complexity, one of the most complex part of POPMUSIC template is to find an initial solution. This article presents a method for generating an appropriate initial solution to the location-rout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…With these definitions the GSPP formulation of the BAP presented in [3] is stated as follows. minimize w∈Ω c w x w (1) subject to…”
Section: Generalized Set-partitioning Problem Formulationmentioning
confidence: 99%
“…With these definitions the GSPP formulation of the BAP presented in [3] is stated as follows. minimize w∈Ω c w x w (1) subject to…”
Section: Generalized Set-partitioning Problem Formulationmentioning
confidence: 99%
“…For example, it is not clear how to meaningfully order the subproblems. One early work in this direction demonstrated that a last-in-first-out stack order performs better than random [3].…”
Section: Related Workmentioning
confidence: 99%
“…Matheuristics have been used successfully in routing problems [3]. In this context, POPMUSIC has been successfully utilized in various studies associated with the VRP (see [2,22,29]) for address large instances by decomposing them into a set of parts.…”
Section: Related Workmentioning
confidence: 99%